COMPARATIVE STUDY BETWEEN THE EFFECT OF TRICHODERMA VIRIDE AND DIFENOCONAZOLE TO INHIBIT GROWTH MYCELIAL Of FUSARIUM OXYSPORUM (Journal of Sciences & Technology, 2020)
Direct confrontation tests between T. viride and F. oxysporum on agar medium (PDA) revealed considerable activity by the biocontrol agent on the pathogen. After six days of incubation, the average diameter of the pathogen colony was 26 mm and the percent of inhibition was 63.83% relative to the control with 71 mm. At the end of the eighth day, T. viride completely invades the F. oxysporum colony and sporulates on it.The results of the test fungicide revealedmoderate inhibition of mycelial growth of the pathogen, so the concentration of 300 ppm was considered a threshold of inhibition of mycelial growth of F. oxysporum, which appeared sensitive.Otherwise, F.oxysporum appeared resistant against the different concentrations (30 and 3) ppm of Difenoconazole.According to literature and several studies carried out in this field, it has been concluded that T. viride is very effective against pathogenicity of F.oxysporum, whereas the use of fungicide (Difenoconazole) is effective but with varying degrees.